A Review of Rafting Tourism Management - Zikrur Rahmat; Devi Catur Winata (Journal Management of Sport, 2023)
This research originated from observations and also field observations made by researchers in the Sipispis sub-district of Serdang Bedagai Regency. Researchers consider that in Sipispis District, Serdang Bedagai Regency has a Recreational Sports Management of rafting in the sub-district. Existing planning is expected to be utilized as well as possible for rafting athletes and tourism for regional development and also as a regional promotion so that it can be recognized by the wider community. Researchers consider that it is not only the potential for Rafting Sports that is found in Sipispis District, Serdang Bedagai Regency, but there are also potentials such as culture, kincia attractions, culinary, tubing, as well as the potential for hidden waterfall tourism which is only done by rafting or tubing on the Ombiilin River, Sipispis District, Serdang Bedagai Regency. This type of research is qualitative, the subject in this study is a review of the management of Royal Crown Adventure Club recreational sports on the Bah Bolon River, Sipispis sub-district, Serdang Bedagai district by conducting interviews, observation, and documentation.